Calorimetric evidence for enhancement of homogeneity in high performance Sr1-xKxFe2As2 superconductors. (September 2017) - Dong, Chiheng; Yao, Chao; Huang, He; Zhang, Xianping; Wang, Dongliang; Ma, Yanwei
Abstract: We comparatively studied the critical current density, magnetization and specific heat of the rolled and the hot-pressed Sr1 −  x K x Fe2 As2 tapes. The Schottky anomaly that is obvious in the specific heat of the rolled tape disappears in the hot-pressed tape. Moreover, the hot-pressed tape has a higher fraction of superconductivity and a narrower distribution of superconducting transition temperature than the rolled tape. Combined with the magnetization data, we conclude that sintering under high pressure provides a better environment for complete chemical reaction and more homogenous dopant distribution, which is beneficial to the global current of a superconductor. Graphical abstract: